HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DAN KOORDINASI MATA TANGAN DENGAN KETEPATAN SMASH DALAM PERMAINAN BOLA VOLI PADA ATLIT LASKAR PEKANBARU - Tawilah, Imron; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: The subject matter in this research lays in the failure which happens when doing smash to the volley ball; hypothetically, the causing factor is the player’s physical condition such as the explosive power of arm muscle and shoulder, the coordination between the hand-eye. The research is conducted in order to discover if there is any relation between the explosive power of arm muscle and shoulder and hand-eye coordination with the speed of smash in volleyball game on Laskar Pekanbaru’s athletes. The sample in this research is the athletes of Laskar Pekanbaru as many as 12 people. The method used in taking the sample is total sampling. Two-hand medicine ball put test is applied on the research as the instrument, which aimed to know the explosive power of arm muscle and shoulder. Therefore, a tennis ball catching and throwing test intends to measure hand-eye coordination and then test the accuracy of the smash as a mean to measure smash / spike skills for attacks on targets quickly and directed. Subsequently, the data is processed statistically in order to examine the normalcy with lilifors test on significant level α0,05. Based on the result of the research, hence, it can be concluded that; the result which obtained from explosive power of arm muscle and shoulder do not have any significant relation with the speed of smash in volleyball game on LaskarPekanbaru’s athletes caused of rcount(0,575) <rtab(0,576), the result of hand-eye coordination shows that there is no substantial relation with the speed of smash in volleyball game on LaskarPekanbaru’s athletes caused of rcount(0,117) <rtab(0,576), there is a significant relation jointly between the explosive power of arm muscle and shoulder and hand-eye coordination with the precision of a smash in volleyball game onLaskarPekanbaru’s athletes rcount(0,576) >Rtabel (0,576). Keywords: Explosive power, Arm Muscle And Shoulder, Hand-Eye Coordination, Smash Speed